AL-TARJAMAH AL-FAURIYYAH METHOD WITH COGNITIVE LEARNING THEORY IN SPEAKING SKILLS LEARNING - Salimatul Fuadah (ALSINATUNA, 2021)
Learning is a business process that involves mental activities that occur with it the process of active interaction with the environment in the form of knowledge, understanding, behavior, as well as in learning Arabic that requires deep methods the learning. This article aims to examine the methods of al-tarjamah al-fauriyyah that cognitive theory-based learning can be used in speaking skills learning. An article this is characterized by the literature review, data is extracted through literature study. The results of the analysis of this article found that the al-tarjamah al-fauriyyah method is a method that uses cognitive learning theory, and can be used effectively in speaking skills learning.